FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM (PADA PERUSAHAAN INDEKS LQ-45 DI BURSA EFEK INDONESIA 2017-2020) - Imam Malik (Negotium: Jurnal Ilmu Administrasi Bisnis, 2022)
The purpose of this study is to ascertain how the price-earnings ratio, earnings per share, and debt-to-equity ratio affect stock returns on the Indonesia Stock Exchange. This study used a quantitative research method as its methodology. The financial statements of LQ-45 firms listed on the Indonesia Stock Exchange (IDX) for the years 2017 through 2020 are the source of the data. Companies on the LQ-45 index listed on the Indonesia Stock Exchange make up the study's sample. The study's findings indicate that, with a regression coefficient of 0.002, the price earning ratio has a positive and significant impact on stock returns. Earnings per share (EPS) has a positive and significant impact on since its regression coefficient is equivalent to 4.761. The earnings per share (EPS) regression coefficient is equal to 4.761, indicating a positive and substantial relationship between EPS and stock returns. A regression coefficient of 0.013 shows a positive and substantial relationship between the debt to equity ratio and stock performance. The coefficient of determination is 31.5%, while additional factors not included in this study have an impact on the remaining 68.5%.